A companion to the English Dominican province: from its beginnings to the Reformation - Giraud, Eleanor J.; Linde, Cornelia (Brill's companions to the Christian tradition, 2021)
"A Companion to the Dominican Order in England offers an account of Dominican activities in England, Ireland, Scotland and Wales from their arrival in 1221 until their dissolution at the Reformation. Over the three centuries covered in this volume, the Friars Preachers not only devoted themselves to the cure of souls via preaching and hearing confessions, but they also represented English kings on diplomatic missions, influenced politics and society, and contributed to cultural, intellectual and religious life across the British Isles"--